An example implementation of STEM in preschool education: Carrying eggs without breaking. (2nd January 2020) - Ültay, Neslihan; Aktaş, Banu
Abstract: Although there are many examples of activities for using STEM in the preschool education, the number of studies on how these activities can be used in practice, how children can react, and what kind of products they can design are limited. The aim of this study is to implement the STEM activity called "How do I carry the eggs without breaking?" which is planned for 48-66-month-old children and to convey the implementation stages in order to set an example for other researchers. Because there is no any guidelines or models about implementation of STEM activities, we set out 7 steps from STEM-oriented studies, which are shown in detail in the study, have been formed by focusing on the points that should be at an STEM activity. During all the steps of the activity, students cooperatively worked in groups and their social relations were improved. While children were trying to test their designs by carrying real eggs, they had fun because in the designation process they used ping-pong balls. At the testing stage, some designs of the groups could not have carried the eggs and they were broken. The teacher had guided them to test the new ideas on redesign.